On The Determination of a Convex Sequence of Signals by Absolute Sum of Factors of Trigonometric Series - Sahani, Suresh Kumar; Tiwari, S.K.; Sonat, B.; Poudel, Madhav Prasad (The Nepali Mathematical Sciences Report, 2024)
Five theorems on the identification of a convex sequence of signals via the absolute sum of elements of trigonometric series are established in this study. Several well-known results are specific cases of these theorems. When the function has bounded variation, it also addresses several special circumstances of fuzzy numbers.